2023
DOI: 10.3389/fpubh.2023.1115055
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and susceptibility of non-albicans Candida isolated from various clinical specimens in Lebanese hospitals

Abstract: BackgroundInvasive fungal infections have presented a challenge in treatment. In the past, it was known that the frontrunner in such infections is Candida albicans with little emphasis placed on non-albicans Candida species (NAC). Studies worldwide have shown a rise in fungal infections attributed to non-albicans Candida species. The aim of this study is to describe the epidemiology of NAC infections along with an overview of resistance in Lebanese hospitals.MethodsThis is a two-year observational multi-centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Among the total study population (n=44), Candida tropicalis was found to be the dominant isolate (41%), followed by Candida albicans (23%). Similar Candida non-albicans trends have been isolated and observed in various studies [11][12][16][17][18][19][20], whereas other research shows a pervasiveness of Candida glabrata and Candida albicans [21][22][23][24]. Phospholipase occurrence and biofilm emergence have been identified as important virulence determinants in Candida tropicalis, both of which contribute to pathogenic organisms in candidemia patient populations [20,25].…”
Section: Discussionsupporting
confidence: 72%
“…Among the total study population (n=44), Candida tropicalis was found to be the dominant isolate (41%), followed by Candida albicans (23%). Similar Candida non-albicans trends have been isolated and observed in various studies [11][12][16][17][18][19][20], whereas other research shows a pervasiveness of Candida glabrata and Candida albicans [21][22][23][24]. Phospholipase occurrence and biofilm emergence have been identified as important virulence determinants in Candida tropicalis, both of which contribute to pathogenic organisms in candidemia patient populations [20,25].…”
Section: Discussionsupporting
confidence: 72%
“…[36][37][38] Various studies performed in recent years on the antifungal resistance in NCAC have proved the same. 39 The present study reported 41.76% prevalence of C. albicans. 24.27% of C. glabrata, 20.88% of C. krusei and 8.79% of C. tropicalis and 4.39% of C. parapsilosis were isolated among NCAC.…”
Section: Discussionsupporting
confidence: 51%
“…One interesting but unexpected aspect of our study is the rate of isolate-misidentification 50. All our isolates were labeled by our tertiary care center as C. parapsilosis [ 11 ]. However, based on our whole genome sequencing data a significant percentage of our isolates- 3 out of 9- were misidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Nine C. parapsilosis hospital isolates were obtained from the Lebanese American University Medical Center, Rizk Hospital, Beirut in Lebanon. Species identification and broth microdilution antifungal susceptibility testing ( Table 1 ) was performed by Husni et al [ 11 ]. Four out of nine isolates were resistant to fluconazole, designated as isolates R1, R2, R3 and R4 and the five others designated as isolates S1, Ca, Co, S2 and Cm were sensitive to fluconazole.…”
Section: Methodsmentioning
confidence: 99%